Performance Evaluation and Organization’s Culture Impacts on Job Satisfaction and Employees’ Performance - Nurdjanah Hamid; Agus Yulianto; Amiruddin Amrullah; Siti Haerani (Faculty of Economics and Business, Hasanuddin University, 2017)
Abstract: The study investigates and evaluates impacts of performance evaluation and company’s culture on job satisfaction and employees’ performance. Method of data collection is using questionnaire. Data was analyzed by path analysis with decomposition model of causal influence between variables. The results indicate that the influence of two variables - performance evaluation and Company’s culture have direct and indirect effect to employees’ performance. The other variable (job satisfaction) has direct effect to employees’ performance.